Why vaccines fail against Piscirickettsiosis in farmed salmon and trout and how to avoid it: A review - Valenzuela-Aviles, Paula; Torrealba, Débora; Figueroa, Carolina; Mercado, Luis; Dixon, Brian; Conejeros, Pablo; Gallardo-Matus, José (Frontiers in Immunology, 2022)
Piscirickettsiosis is the most severe, persistent, and damaging disease that has affected the Chilean salmon industry since its origins in the 1980s. As a preventive strategy for this disease, different vaccines have been developed and used over the last 30 years. However, vaccinated salmon and trout frequently die in the sea cages and the use of antibiotics is still high demonstrating the low efficiency of the available vaccines. The reasons why the vaccines fail so often are still debated, but it could involve different extrinsic and intrinsic factors. Among the extrinsic factors, mainly associated with chronic stress, we can distinguish: 1) biotic including coinfection with sea lice, sealions attacks or harmful algal blooms; 2) abiotic including low oxygen or high temperature; and 3) farm-management factors including overcrowding or chemical delousing treatments. Among the intrinsic factors, we can distinguish: 1) fish-related factors including host's genetic variability (species, population and individual), sex or age; 2) pathogen-related factors including their variability and ability to evade host immune responses; and 3) vaccine-related factors including low immunogenicity and poor matches with the circulating pathogen strain. Based on the available evidence, in order to improve the development and the efficacy of vaccines against P. salmonis we recommend: a) Do not perform efficacy evaluations by intraperitoneal injection of pathogens because they generate an artificial protective immune response, instead cohabitation or immersion challenges must be used; b) Evaluate the diversity of pathogen strains in the field and ensure a good antigenic match with the vaccines; c) Investigate whether host genetic diversity could be improved, e.g. through selection, in favor of better and longer responses to vaccination; d) To reduce the stressful effects at the cage level, controlling the co-infection of pathogens and avoiding fish overcrowding. To date, we do not know the immunological mechanisms by which the vaccines against P. salmonis may or may not generate protection. More studies are required to identify what type of response, cellular or molecular, is required to develop effective vaccines.